Supporting local diversity of habitats and species on farmland: a comparison of three wildlife‐friendly schemes. Issue 1 (18th November 2015) - Hardman, Chloe J.; Harrison, Dominic P.G.; Shaw, Pete J.; Nevard, Tim D.; Hughes, Brin; Potts, Simon G.; Norris, Ken
Summary: Restoration and maintenance of habitat diversity have been suggested as conservation priorities in farmed landscapes, but how this should be achieved and at what scale are unclear. This study makes a novel comparison of the effectiveness of three wildlife‐friendly farming schemes for supporting local habitat diversity and species richness on 12 farms in England. The schemes were: (i) Conservation Grade (Conservation Grade: a prescriptive, non‐organic, biodiversity‐focused scheme), (ii) organic agriculture and (iii) a baseline of Entry Level Stewardship (Entry Level Stewardship: a flexible widespread government scheme). Conservation Grade farms supported a quarter higher habitat diversity at the 100‐m radius scale compared to Entry Level Stewardship farms. Conservation Grade and organic farms both supported a fifth higher habitat diversity at the 250‐m radius scale compared to Entry Level Stewardship farms. Habitat diversity at the 100‐m and 250‐m scales significantly predicted species richness of butterflies and plants. Habitat diversity at the 100‐m scale also significantly predicted species richness of birds in winter and solitary bees. There were no significant relationships between habitat diversity and species richness for bumblebees or birds in summer. Butterfly species richness was significantly higher on organic farms (50% higher) and marginally higher on Conservation Grade farms (20% higher), compared with farms in Entry Level Stewardship. Organic farms supported significantly more plant species than Entry Level Stewardship farms (70% higher) but Conservation Grade farms did not (10% higher). There were no significant differences between the three schemes for species richness of bumblebees, solitary bees or birds. Policy implications . The wildlife‐friendly farming schemes which included compulsory changes in management, Conservation Grade and organic, were more effective at increasing local habitat diversity and species richness compared with the less prescriptive Entry Level Stewardship scheme. We recommend that wildlife‐friendly farming schemes should aim to enhance and maintain high local habitat diversity, through mechanisms such as option packages, where farmers are required to deliver a combination of several habitats.